Spontaneous skyrmion conformal lattice and transverse motion during dc and ac compression - Bellizotti Souza, J. C. [UNESP]; Vizarim, N. P. [UNESP]; Reichhardt, C. J.O.; Reichhardt, C.; Venegas, P. A. [UNESP] (IOP Publishing, 2023)
We use atomistic-based simulations to investigate the behavior of ferromagnetic skyrmions being continuously compressed against a rigid wall under dc and ac drives. The compressed skyrmions can be annihilated close to the wall and form a conformal crystal with both a size and a density gradient, making it distinct from conformal crystals observed previously for superconducting vortices and colloidal particles. For both dc and ac driving, the skyrmions can move transverse to the compression direction due to a combination of density and size gradients. Forces in the compression direction are converted by the Magnus force into transverse motion. Under ac driving, the amount of skyrmion annihilation is reduced and we find a skyrmion Magnus ratchet pump. We also observe shear banding in which skyrmions near the wall move up to twice as fast as skyrmions further from the wall. When we vary the magnitude of the applied drive, we find a critical current above which the skyrmions are completely annihilated during a time scale that depends on the magnitude of the drive. By varying the magnetic parameters, we find that the transverse motion is strongly dependent on the skyrmion size. Smaller skyrmions are more rigid, which interferes with the size gradient and destroys the transverse motion. We also confirm the role of the size gradient by comparing our atomistic simulations with a particle-based model, where we find that the transverse motion is only transient. Our results are relevant for applications where skyrmions encounter repulsive magnetic walls, domain walls, or interfaces.
Keywords: compression; conformal crystal; skyrmion